α-Synuclein-mediated mitochondrial translocation of cofilin-1 leads to oxidative stress and cell apoptosis in PD - Yan, Mingmin; Zhang, Qian; Chen, Yu; Zhu, Chenyi; Wang, Dan; Tan, Jie; He, Bihua; Li, Qin; Deng, Xiaorong; Wan, Yue (Frontiers in Neuroscience, 2024)
Parkinson’s disease (PD) is characterized by the accumulation of misfolded α-synuclein protein and loss of dopaminergic neurons in the substantia nigra. Abnormal α-synuclein aggregates form toxic Lewy bodies and finally induce neuronal injury. Mitochondrial dysfunction was reported to be involved in the neurotoxicity of α-synuclein aggregates in PD. However, the specific mechanism by which abnormal α-synuclein aggregates exert mitochondrial disorders remains poorly defined. Previously we found that cofilin 1, a member of the actin-binding protein, regulates α-synuclein pathogenicity by promoting its aggregation and spreading in vitro and in vivo. Here we further investigated the effect of cofilin 1 on α-synuclein induced mitochondrial damage. We discovered that α-synuclein aggregates accelerate the translocation of cofilin 1 to mitochondria, then promote its combination with mitochondrial outer membrane receptor Tom 20, and ultimately activate the oxidative damage and apoptosis pathway in mitochondria. All these results demonstrate the important regulatory role of cofilin 1 in the mitochondrial neurotoxicity of pathological α-synuclein during the progression of PD.